Juridical Analysis of the Cooperation Agreement between CV. Hot Pepper Creative and National Health Analyst Vocational School Surakarta Based on Contract Law - Roi Hartono Putro; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2023)
Some large companies with good capital and capabilities will also provide good services and administrative systems. Maybe it will be different if the company is still relatively small and within the scope of a relatively small company running its company only with original or perfunctory capital, which makes the company not have employees who have sufficient competence in managing the company. This study aims to determine the provisions in the cooperation agreement letter between CV Hot pepper Creative and SMK National Health Analyst Surakarta and whether it is by the legal regulations of the agreement. The author uses legal (doctrinal) research methods carried out by searching library materials. The author’s research type in this study is normative legal research. The data types used are primary legal materials consisting of legal regulations, secondary legal materials derived from books, research journals, and other research, and tertiary materials derived from Indonesian and legal dictionaries. The results of the research obtained that the contract agreement carried out between Hot pepper and SMK Analis was by the legal terms of the agreement Article 1320 KUHPerdata. The contractual agreement is by the principle of freedom of contract Article 1324 KUHPerdata that there is no coercion either by physical violence or intimidation so that the person is forced to agree to the agreement.